Financial statement analysis - Wild, John J.; Subramanyam, K. R.; Halsey, Robert F. (New Delhi : Tata McGraw Hill Education Private Limited, 2007)
Financial Statement Analysis, 9e, emphasizes effective business analysis and decision making by analysts, investors, managers, and other stakeholders of the company. It continues to set the standard (over 8 prior editions and hundreds of thousands in unit book sales) in showing students the keys to effective financial statement analysis. It begins with an overview (chapters 1-2), followed by accounting analysis (chapters 3-6) and then financial analysis (chapters 7-11). The book presents a balanced view of analysis, including both equity and credit analysis, and both cash-based and earnings-based valuation models. The book is aimed at accounting and finance classes, and the professional audience as it shows the relevance of financial statement analysis to all business decision makers. The authors: 1. Use numerous and timely (3z(Breal world(3y (Bexamples and cases 2. Draw heavily on actual excerpts from financial reports and footnotes 3. Focus on analysis and interpretation of financial reports and their footnotes 4. Illustrate debt and equity valuation that uses results of financial statement analysis 5. Have a concise writing style to make the material accessible s
Ch.1. Overview of Financial Statement Analysis -- Ch.2. Financial Reporting and Analysis -- Ch.3. Analyzing Financing Activities -- Ch.4. Analyzing Investing Activities -- Ch.5. Analyzing Investing Activities: Intercorporate Investment -- Ch.6. Analyzing Operating Activities -- Ch.7. Cash Flow Analysis -- Ch.8. Return on Invested Capital and Profitability Analysis -- Ch.9. Prospective Analysis -- Ch.10. Credit Analysis -- Ch.11. Equity Analysis and Valuation.
Includes bibliographical references and index.
Keywords: Financial statements